Changes in Heart Rate Variability of Depressed Patients after Electroconvulsive Therapy. (27th August 2012) - Royster, Erica B.; Trimble, Lisa M.; Cotsonis, George; Schmotzer, Brian; Manatunga, Amita; Rushing, Natasha N.; Pagnoni, Giuseppe; Auyeung, S. Freda; Brown, Angelo R.; Schoenbeck, Joel; Murthy, Smitha; McDonald, William M.; et al.
Abstract : Objective. As few, small studies have examined the impact of electroconvulsive therapy (ECT) upon the heart rate variability of patients with major depressive disorder (MDD), we sought to confirm whether ECT-associated improvement in depressive symptoms would be associated with increases in HRV linear and nonlinear parameters. Methods. After providing consent, depressed study participants (n = 21 ) completed the Beck Depression Index (BDI), and 15-minute Holter monitor recordings, prior to their 1st and 6th ECT treatments. Holter recordings were analyzed for certain HRV indices: root mean square of successive differences (RMSSD), low-frequency component (LF)/high-frequency component (HF) and short-(SD1) versus long-term (SD2) HRV ratios. Results. There were no significant differences in the HRV indices of RMSDD, LF/HF, and SD1/SD2 between the patients who responded, and those who did not, to ECT. Conclusion. In the short term, there appear to be no significant improvement in HRV in ECT-treated patients whose depressive symptoms respond versus those who do not. Future studies will reveal whether diminished depressive symptoms with ECT are reliably associated with improved sympathetic/parasympathetic balance over the long-term, and whether acute changes in sympathetic/parasympathetic balance predict improved mental- and cardiac-related outcomes.